2006
DOI: 10.1073/pnas.0509996103
|View full text |Cite
|
Sign up to set email alerts
|

Specific recognition and accelerated uncoating of retroviral capsids by the TRIM5α restriction factor

Abstract: The host restriction factor TRIM5␣ mediates species-specific, early blocks to retrovirus infection; susceptibility to these blocks is determined by viral capsid sequences. Here we demonstrate that TRIM5␣ variants from Old World monkeys specifically associate with the HIV type 1 (HIV-1) capsid and that this interaction depends on the TRIM5␣ B30.2 domain. Human and New World monkey TRIM5␣ proteins associated less efficiently with the HIV-1 capsid, accounting for the lack of restriction in cells of these species.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

39
898
3
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 664 publications
(944 citation statements)
references
References 60 publications
39
898
3
4
Order By: Relevance
“…14 Restriction by TRIM5a is initiated by physical recognition of incoming retroviruses by TRIM5a proteins. 15,16 This interaction occurs within the first hours after virus entry. 17 and involves determinants present in the N-terminal domain of the capsid proteins that constitute the retroviral outer core structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Restriction by TRIM5a is initiated by physical recognition of incoming retroviruses by TRIM5a proteins. 15,16 This interaction occurs within the first hours after virus entry. 17 and involves determinants present in the N-terminal domain of the capsid proteins that constitute the retroviral outer core structure.…”
Section: Introductionmentioning
confidence: 99%
“…Viral cores seem to undergo accelerated uncoating, as evidenced by the disappearance of capsid in particulate form. 16,21,22 The proteasome is also involved and causes a decrease in retroviral complementary DNA accumulation in acutely infected cells. 23 TRIM5a proteins can seemingly selfubiquitinate 24,25 and are rapidly degraded by the proteasome on exposure to a restriction-sensitive virus.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] This SPRY domain interacts with the capsid core of the virus, and in the case of the rhesus macaque variant of TRIM5a (rhTRIM5a), interaction with the capsid core of HIV-1 normally leads to a block in infectivity prior to the completion of reverse transcription. [5][6][7] Members of the TRIM family of proteins have been shown to self-associate through coiled-coiled domains into higherorder oligomers, [8][9][10] and many members of this family accumulate in discrete subcellular structures. 11 Studies examining the subcellular localization of rhTRIM5a revealed that this protein localizes in two cytoplasmic populations, but these populations are dynamic and are capable of exchanging protein.…”
Section: Introductionmentioning
confidence: 99%
“…The rhesus macaque TRIM5a ortholog (TRIM5a Rhe ) has been shown to bind to the human immunodeficiency virus type 1 (HIV-1) capsid and lead to premature viral uncoating. 6 Restriction by TRIM5a Rhe is enhanced by the presence of cellular cyclophilin A (CypA) protein, although CypA is not absolutely required for restriction in rhesus macaque cells. 7 Knockdown of CypA with small interfering RNA (siRNA) or its inhibition by cyclosporin A (CsA) can partially overcome TRIM5a-mediated restriction.…”
Section: Introductionmentioning
confidence: 99%